2006
DOI: 10.1002/chin.200651191
|View full text |Cite
|
Sign up to set email alerts
|

Hassallidin B — Second Antifungal Member of the Hassallidin Family.

Abstract: Hassallidin B -Second Antifungal Member of the Hassallidin Family. -Hassallidin B (I), isolated from the biomass of the cyanobacterium Hassallia sp., exhibits the same peptidic and fatty acid core as the known natural product hassallidin A. In contrast to hassallidin A compound (I) possesses an additional carbohydrate unit, linked to the lipid unit and identified as rhamnose. The antifungal activity of (I) suggest that this compound shows a similar mode of action as hassallidin A. However, due to the additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Methyl oxazole and thiazole moieties of microcyclamides, chlorinated carbon and methylated nitrogen in the β ‐carboline skeleton of nostocarboline, the cyclo structure of thiazoles bound amino acids of aeruginazole A, Dht and Dhb of hassallidins A and B, methyloxoazoline, thiazole and thiazoline of aerucyclamides, the guanidine group in the scalarane skeleton of scytoscalarol, the hapalindole skeleton of ambiguine isonitriles are the key components imparting the bioactivities to these metabolites (Bonazzi et al ., ; Neuhof et al ., , ; Mo et al ., ; Raveh and Carmeli, ). Although cyanobacteria are considered to be the prolific producers of secondary metabolites with biomedical potentials, obviously none of the cyanobacterial natural product has cleared all the clinical trials and has launched for therapeutic use.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methyl oxazole and thiazole moieties of microcyclamides, chlorinated carbon and methylated nitrogen in the β ‐carboline skeleton of nostocarboline, the cyclo structure of thiazoles bound amino acids of aeruginazole A, Dht and Dhb of hassallidins A and B, methyloxoazoline, thiazole and thiazoline of aerucyclamides, the guanidine group in the scalarane skeleton of scytoscalarol, the hapalindole skeleton of ambiguine isonitriles are the key components imparting the bioactivities to these metabolites (Bonazzi et al ., ; Neuhof et al ., , ; Mo et al ., ; Raveh and Carmeli, ). Although cyanobacteria are considered to be the prolific producers of secondary metabolites with biomedical potentials, obviously none of the cyanobacterial natural product has cleared all the clinical trials and has launched for therapeutic use.…”
Section: Resultsmentioning
confidence: 99%
“…Such compounds may face hindrance in reaching their targets. Neuhof et al (2005Neuhof et al ( , 2006 isolated potent antifungal glycosylated lipopeptides, hassallidin A and B, from epilithic Italian cyanobacterium, Hassallia sp. These peptides contain amino acids, fatty acid and carbohydrate moieties (Fig.…”
Section: Antipathogenic Metabolitesmentioning
confidence: 99%
“…Nevertheless, previous studies have shown that there is no correlation between phosphatase inhibitors and apoptogenic activity against SH-SY5Y-neuroblastoma and AML cells [58,63]. The lipopeptides hassallidin and puwainaphycin have been previously shown to have cytotoxic activity [64,65]. Aeruginosin and anabaenopeptin are protease inhibitors with no reported cytotoxic effects.…”
Section: Discussionmentioning
confidence: 97%
“…The hassallidins, first isolated from Tolypothrix [136,137], were found to be widespread among filamentous cyanobacteria [138]. They are structurally interesting non-ribosomal cyclic depsipeptides decorated with both a sugar and a dihydroxy fatty acid that can also be glycosylated.…”
Section: Antifungal Metabolitesmentioning
confidence: 99%
“…They are structurally interesting non-ribosomal cyclic depsipeptides decorated with both a sugar and a dihydroxy fatty acid that can also be glycosylated. The MICs of hassallidins A (12) to D against various Candida species including C. albicans are in the range from 1.5 to 10.5 µM [137,138]. Cytotoxicity of the hassallidins is about 10-fold higher [139].…”
Section: Antifungal Metabolitesmentioning
confidence: 99%